Mtr10p functions as a nuclear import receptor for the mRNA‐binding protein Npl3p - Senger, Bruno; Simos, Geōrgios; Bischoff, F. Ralf; Podtelejnikov, Alexandre; Mann, Matthias; Hurt, Ed (The EMBO journal, 1998)
MTR10, previously shown to be involved in mRNA export, was found in a synthetic lethal relationship with nucleoporin NUP85. Green fluorescent protein (GFP)‐tagged Mtr10p localizes preferentially inside the nucleus, but a nuclear pore and cytoplasmic distribution is also evident. Purified Mtr10p forms a complex with Npl3p, an RNA‐binding protein that shuttles in and out of the nucleus. In mtr10 mutants, nuclear uptake of Npl3p is strongly impaired at the restrictive temperature, while import of a classic nuclear localization signal (NLS)‐containing protein is not. Accordingly, the NLS within Npl3p is extended and consists of the RGG box plus a short and non‐repetitive C‐terminal tail. Mtr10p interacts in vitro with Gsp1p‐GTP, but with low affinity. Interestingly, Npl3p dissociates from Mtr10p only by incubation with Ran‐GTP plus RNA. This suggests that Npl3p follows a distinct nuclear import pathway and that intranuclear release from its specific import receptor Mtr10p requires the cooperative action of both Ran‐GTP and newly synthesized mRNA.
Gesehen am 01.12.2025